Comparative 3D ultrastructure of Plasmodium falciparum gametocytes - Felix Evers; Rona Roverts; Cas Boshoven; Mariska Kea-te Lindert; Julie M. J. Verhoef; Nico Sommerdijk; Robert E. Sinden; Anat Akiva; Taco W. A. Kooij (Nature Communications)
Abstract Despite the enormous significance of malaria parasites for global health, some basic features of their ultrastructure remain obscure. Here, we apply high-resolution volumetric electron microscopy to examine and compare the ultrastructure of the transmissible male and female sexual blood stages of Plasmodium falciparum as well as the more intensively studied asexual blood stages revisiting previously described phenomena in 3D. In doing so, we challenge the widely accepted notion of a single mitochondrion by demonstrating the presence of multiple mitochondria in gametocytes. We also provide evidence for a gametocyte-specific cytostome, or cell mouth. Furthermore, we generate the first 3D reconstructions of the parasite’s endoplasmic reticulum (ER) and Golgi apparatus as well as gametocyte-induced extraparasitic structures in the infected red blood cell. Assessing interconnectivity between organelles, we find frequent structural appositions between the nucleus, mitochondria, and apicoplast. We provide evidence that the ER is a promiscuous interactor with numerous organelles and the trilaminar pellicle of the gametocyte. Public availability of these volumetric electron microscopy resources will facilitate reinterrogation by others with different research questions and expertise. Taken together, we reconstruct the 3D ultrastructure of P. falciparum gametocytes at nanometre scale and shed light on the unique organellar biology of these deadly parasites.